Parental attachment and problematic smartphone use in adolescents: the chain-mediated role - Peng, Yuan; Cui, Wenhua; Yang, Ruqian; Wang, Hua (Frontiers in Psychology, 2025)
AimThis study explores how parental attachment influence adolescents’ problematic smartphone use (PSU), examining the chain mediating roles of peer attachment and online need satisfaction in this relationship.MethodsA chain mediation analysis was conducted using data collected from a sample of 1,208 adolescents who completed questionnaires assessing parent/peer attachment, online need satisfaction, and PSU.ResultsThe results showed that (1) parental attachment were negatively associated with PSU; (2) parental attachment influenced PSU through the mediating effect of peer attachment; (3) parental attachment influenced PSU through the mediating effect of online need satisfaction; and (4) peer attachment and online need satisfaction played a chain mediating role in the influence of parental attachment on adolescents PSU.ConclusionThese findings can help researchers and educators better understand the underlying mechanisms of the relationship between parent and adolescents on PSU and to provide practical and effective operational suggestions for the prevention and intervention of PSU among adolescents.